Protein solubility prediction using CNN and CNN-LSTM hybrid models - Sysoykova, Ekaterina (Jihočeská univerzita, 2022)
Protein solubility prediction based on the raw amino acid sequence using three machine/deep learning techniques: RF, CNN, and a hybrid CNN-biLSTM model. Assessment of the performance difference between the models with evaluation metrics and statistical significance tests.
Protein solubility prediction using CNN and CNN-LSTM hybrid models
Keywords: protein solubility; machine learning; deep learning; CNN; LSTM; protein solubility; machine learning; deep learning; CNN; LSTM